2016
DOI: 10.1093/bja/aew021
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum haemorrhage related early increase in D-dimers is inhibited by tranexamic acid: haemostasis parameters of a randomized controlled open labelled trial

Abstract: ISRCTN09968140.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 39 publications
(57 reference statements)
0
43
0
1
Order By: Relevance
“…The working group of Ducloy-Bouthors [50] showed that the therapeutic application of TxA in bleeding PPH patients caused a significant reduction of blood loss, of patients with a haemoglobin decrease > 4 g/dl, a reduction of the number of transfused RBCs and a shorter bleeding duration. Analysing these study's haemostasis parameter provided biological evidence of an early increase in D-dimers and plasmin-antiplasmin complexes associated with active PPH and its attenuation by the early use of TxA [51]. The publication of the WOMAN (World Maternal Antifibrinolytic) trial will hopefully add further knowledge concerning the combination of TxA and PPH [52].…”
Section: Haemostasis and Coagulation Managementmentioning
confidence: 94%
“…The working group of Ducloy-Bouthors [50] showed that the therapeutic application of TxA in bleeding PPH patients caused a significant reduction of blood loss, of patients with a haemoglobin decrease > 4 g/dl, a reduction of the number of transfused RBCs and a shorter bleeding duration. Analysing these study's haemostasis parameter provided biological evidence of an early increase in D-dimers and plasmin-antiplasmin complexes associated with active PPH and its attenuation by the early use of TxA [51]. The publication of the WOMAN (World Maternal Antifibrinolytic) trial will hopefully add further knowledge concerning the combination of TxA and PPH [52].…”
Section: Haemostasis and Coagulation Managementmentioning
confidence: 94%
“…Increased fibrinolysis and platelet activation are observed, as well as a substantial release of tissue factor into the maternal blood stream, which may also activate consumption of procoagulant factors (12). Tranexamic acid administration has been shown to stabilize fibrinolysis and D-dimer liberation in obstetric hemorrhage and may be wellsuited to counter some aspects of the disproportional coagulopathy (13). Prior to publication of the WOMAN trial, several small, randomized trials were conducted on the prophylactic use of tranexamic acid in the setting of cesarean delivery at low-risk for hemorrhage.…”
Section: Editorialmentioning
confidence: 99%
“…[8][9][10] Typically, additional treatment includes antifibrinolytic therapy given the increased fibrinolysis in general associated with hemorrhage from the mucosal uterine surface. 11 Also, data are accruing in favor of antifibrinolytic therapy, 12 as a blood-conserving agent particularly in surgery 13,14 and in menorrhagia.…”
Section: Introductionmentioning
confidence: 99%